Perlindungan Hukum Pemegang Saham Terhadap Tindakan Penarikan Kembali Saham Ditinjau Dari Undang-Undang Perseroan Terbatas - Dimas Pasha Hafidz; Mohammad Rafi Al Farizy (Faculty of Law, University of Jember, Indonesia, 2023)
One of the corporate actions that the Company can take is to reduce capital. Reducing the capital carried out by the Company can be done in 2 ways, namely recalling shares or reducing the nominal value of shares based on Article 47 paragraph (1) of Law Number 40 of 2007. The corporate action to reduce capital must still protect the interests of shareholders. However, the provisions of Law Number 40 of 2007 are still unable to protect the interests of shareholders in terms of corporate actions to reduce capital because there is still legal ambiguity in the phrase